The Effect of Entrepreneurial Orientation and Self-Efficacy on Business Performance with Business Motivation as an Intervening Variable in Snack MSMEs in Ciawi District, Bogor Regency - Dwi Gemina; Palahudin Palahudin; Muhamad Rifky Ramadhan (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of entrepreneurial orientation and self-efficacy on business performance through business motivation as an intervening variable among snack food MSME actors in Ciawi District, Bogor Regency. The research method employed a quantitative approach using primary data collected through questionnaires with a Likert scale of 1–5. The population of this study consisted of snack food MSME actors in Ciawi District, Bogor Regency. The sample included 131 MSME actors aged at least 18 years who had been operating their businesses for more than one year. Data analysis was conducted using the Statistical Product and Service Solution (SPSS). The results indicate that entrepreneurial orientation and self-efficacy have a significant effect on business performance, both directly and indirectly through business motivation as an intervening variable.